Combined effects of neoadjuvant letrozole and zoledronic acid on γδT cells in postmenopausal women with early-stage breast cancer. (April 2018) - Sugie, Tomoharu; Suzuki, Eiji; Yamauchi, Akira; Yamagami, Kazuhiko; Masuda, Norikazu; Gondo, Naomi; Sumi, Eriko; Ikeda, Takafumi; Tada, Harue; Uozumi, Ryuji; Kanao, Shotaro; Tanaka, Yoshimasa; et al.
Abstract: Introduction: Adjuvant bisphosphonates lead to better prognosis in postmenopausal breast cancer. However, the association between clinical outcomes and immune modulation by them is still unclear. Methods: In this prospective, open-label phase II study, postmenopausal women with estrogen receptor-positive and human epidermal growth factor receptor 2-negative early-stage breast cancer received neoadjuvant letrozole (LET) for one month, followed by treatment with a single dose of zoledronic acid. The patients underwent an additional 5 months of treatment with LET prior to surgery. The primary endpoint was the tumor objective response rate (ORR) determined by diameter via MRI. The association between the ORR and γδT cell frequencies was assessed as a secondary endpoint. Results: Out of sixty patients, 55 patients were evaluable for response by MRI. The ORR for LET with zoledronic acid was 38.2% (21/55), which was comparable to that of historical controls (45%). A decrease in the frequency of the Vδ2 T cell subset was observed throughout treatment, and Vδ2 T cells were activated for 6 months. In planned subgroup analyses, patients with low frequencies of Vδ2 T cells prior to zoledronic acid infusion experienced a favorable tumor response compared to those with high frequencies (59.3% [16/27] vs 17.9% [5/28], p = .002). There were no serious adverse events with this treatment regimen. Conclusion: These results showed that neoadjuvant LET with zoledronic acid could not achieve overall effect for local tumor response. However, patients with a low frequency of γδ T cells would benefit from the treatment including zoledronic acid. (UMIN 000008701). Highlights: First study to explore the clinical outcomes and the immune modulatory functions of adjuvant bisphosphonates. Neoadjuvant letrozole plus zoledronic acid decreased the frequency of γδT cells and leads to activation of γδT cells. Postmenopausal breast cancer with a low frequency of γδT cell would benefit from neoadjuvant endocrine therapy combined with zoledronic acid.